Australian Developments in Distance Education and Their Implications for Rural Schools - Ken Stevens (Journal of Research in Rural Education, 1994)
Distance education has for many years played an important role in the delivery of education to rural parts of Australia. Recent developments in information and communication technologies, together with the advent of federallyfunded open learningat the tertiary level, arechallenging traditional notions of distance education in Australia. These developments have many implications for Australian rural educators who must now consider their applications for teachers and learners in remote parts of the country.